Attitudes of Physical Education Teachers towards the Participation of Students with Disabilities in the Physical Education Class in Schools - Aldagamseh, Bayan Izzeddin Mahmoud; Alnuman, Natheir Faisal Mansour; alyasen, Qusai Basem mohammad (International Journal of Membrane Science and Technology, 2023)
The study aimed to reveal the attitudes of physical education teachers towards the participation of students with disabilities in physical education class in schools. The study sample consisted of (208) physical education teachers. The measure of physical education teachers' attitudes towards integrating students with disabilities into the physical education class was applied. The results of the study showed that the general average of the total score for the measure of attitudes towards the participation of students with disabilities in the physical education class was high, with an arithmetic mean of (3.25), and that there were statistically significant differences in the attitudes of physical education teachers towards integrating students with disabilities in the sports class according to the gender no statistically significant differences variable. Academic qualification and educational experience.